Emerging Role of HMGB1 in the Pathogenesis of Schistosomiasis Liver Fibrosis - Vicentino, Amanda Roberta Revoredo (2018)
Universidade Federal do Rio de Janeiro. Instituto de Bioquímica Médica Leopoldo de Meis. Rio de Janeiro, RJ, Brazil